2019
DOI: 10.1186/s13019-019-0910-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential lung ventilation for increased oxygenation during one lung ventilation for video assisted lung surgery

Abstract: Background One lung ventilation (OLV) is the technique used during lung resection surgery in order to facilitate optimal surgical conditions. OLV may result in hypoxemia due to the shunt created. Several techniques are used to overcome the hypoxemia, one of which is continuous positive airway pressure (CPAP) to the non-dependent lung. Another technique is ventilating the non-dependent lung with a minimal volume, thus creating differential lung ventilation (DLV). In this study we compared the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It is a common conception that CPAP applied to the non-ventilated lung in OLV for VATS is likely to disrupt surgical visualization, to the extent that some experts consider CPAP on the non-ventilated lung contraindicated in VATS [ 29 , 30 ]. This belief may have also influenced the design of some studies that investigated the effectiveness of CPAP in VATS as the study designs avoided an alveolar recruitment maneuver prior to application of CPAP [ 31 , 32 ]. Evidence to support the negative effect of CPAP on surgical visualization is mixed: impediment of surgical exposure has been reported in some studies [ 32 ] and refuted in others [ 25 , 33 ].…”
Section: The Role Of Continuous Positive Airway Pressure During Olv In Vatsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a common conception that CPAP applied to the non-ventilated lung in OLV for VATS is likely to disrupt surgical visualization, to the extent that some experts consider CPAP on the non-ventilated lung contraindicated in VATS [ 29 , 30 ]. This belief may have also influenced the design of some studies that investigated the effectiveness of CPAP in VATS as the study designs avoided an alveolar recruitment maneuver prior to application of CPAP [ 31 , 32 ]. Evidence to support the negative effect of CPAP on surgical visualization is mixed: impediment of surgical exposure has been reported in some studies [ 32 ] and refuted in others [ 25 , 33 ].…”
Section: The Role Of Continuous Positive Airway Pressure During Olv In Vatsmentioning
confidence: 99%
“…Evidence to support the negative effect of CPAP on surgical visualization is mixed: impediment of surgical exposure has been reported in some studies [ 32 ] and refuted in others [ 25 , 33 ]. As an alternative to CPAP, some authors have reported effective interventions for hypoxemia during VATS, such as apneic oxygen insufflation of the non-ventilated lung [ 34 ], high frequency jet ventilation [ 33 ], differential ventilation of the non-ventilated lung [ 31 ], and selective lobar oxygen insufflation of the non-ventilated lung using the suction/insufflation channel of the fiberoptic bronchoscope [ 35 ]. A summary of selected studies investigating CPAP during OLV in VATS is shown in Table 1 .…”
Section: The Role Of Continuous Positive Airway Pressure During Olv In Vatsmentioning
confidence: 99%
“…45 Recently, differential lung ventilation has been described whereby the operative lung is ventilated with minimal tidal volumes (TV). 46 If hypoxemia persists, two-lung ventilation should be restored to allow for fiber-optic assessment of the lung isolation device position and the presence of secretions. As a last resort, during open thoracotomy, the surgeon can clamp the pulmonary artery (PA) to the operative lung to reduce the shunt fraction and improve oxygenation.…”
Section: Complications Of One-lung Ventilation Hypoxemiamentioning
confidence: 99%
“…The key to the success of VATS is the maximization of intrathoracic visibility by optimizing the quality of the pulmonary isolation and deflation in a closed thoracic cavity. VATS typically includes lung deflation on the Original Article Effects of bronchial blockers on gas exchange in infants with onelung ventilation: a single-institutional experience of 22 cases surgical side, and one-lung ventilation (OLV) on the nonsurgical side (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%